Fast Prediction of Characteristics in Wound Rotor Synchronous Condenser Using Subdomain Modeling - Manh-Dung Nguyen; Tae-Seong Kim; Kyung-Hun Shin; Gang-Hyeon Jang; Jang-Young Choi (Mathematics)
Wound rotor synchronous condensers (WRSCs) are DC-excited rotor machines that utilize rotor winding instead of permanent magnets. Their voltage regulator controls the rotor field to generate or absorb reactive power, thereby regulating grid voltage or improving power factor. A key characteristic of a WRSC is the compounding curve, which shows the required rotor current under specific stator current and voltage conditions. This paper presents an approach for quickly calculating the electromagnetic parameters of a WRSC using a mathematical method. After determining magnetic flux density, induced voltage, and inductance through analytical methods, the Park and Clarke transformations are applied to derive the dq-frame quantities, enabling prediction of active and reactive powers and compounding curve characteristics. The 60 Hz model was evaluated through comparison with finite element method (FEM) simulations. Results of flux density, induced voltage, and the compounding curve under varying rotor and stator current conditions showed that the proposed method achieved comparable performance to FEM simulation while reducing computational time by half.